2018
DOI: 10.1371/journal.pone.0195264
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of non-cardia gastric cancer with a high serum anti-Helicobacter pylori IgG titer and its association with diffuse-type histology

Abstract: BackgroundData on implications of a high positive titer of serum anti-Helicobacter pylori antibody on gastric cancer (GC) is limited. This study aimed to investigate the characteristics of GC with a high serum anti-H. pylori IgG (Hp-IgG) titer, and its association with diffuse-type GC.MethodsWe analyzed clinical and histological characteristics of 917 non-cardia GC patients who underwent gastrectomy. H. pylori infection was determined serologically by measuring Hp-IgG titer with immunoassay. Seropositive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Epidemiologically, intestinal GC is the most common type, has the highest five-year survival rate, and is more common in men and the elderly. Diffuse-type GC is more likely in women and younger patients and has a lower 5-year survival rate (10)(11)(12). Mix-type has the highest degree of malignancy due to variable biological behavior (13).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologically, intestinal GC is the most common type, has the highest five-year survival rate, and is more common in men and the elderly. Diffuse-type GC is more likely in women and younger patients and has a lower 5-year survival rate (10)(11)(12). Mix-type has the highest degree of malignancy due to variable biological behavior (13).…”
Section: Introductionmentioning
confidence: 99%
“…Mix-type GC possesses all these characteristics (3). The proportion of men and elderly patients is higher in intestinal-type GC, whereas diffuse-type GC is more likely to happen in women and younger patients (4,5). Lauren classification presents differences in etiology, epidemiology and pathology, which means that certain tumor development pathways are characteristics of different Lauren classifications (4,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies have also reported the association of H. pylori infection with the development of DGC [ 120 , 121 , 122 ]. A recent study reported that patients with current infections were prone to developing DGC compared to patients with past infections [ 123 , 124 ]. Similarly, the association of H. pylori was found in 85.36% of DGC [ 125 ].…”
Section: Helicobacter Pylori Infection and Dgcmentioning
confidence: 99%
“…The progression of gastric mucosal atrophy associated with a decrease in H. pylori titer may be attributable to the association between past infection or low H. pylori -IgG titer and IGC [ 123 ]. Gong et al also reported the association of high H. pylori -IgG titer with the development of DGC [ 124 ].…”
Section: Helicobacter Pylori Infection and Dgcmentioning
confidence: 99%